A global, comprehensive review of literature related to paper recycling: A pressing need for a uniform system of terms and definitions. (February 2016) - Ervasti, Ilpo; Miranda, Ruben; Kauranen, Ilkka
Highlights: There is no uniform system of terms and definitions related to paper recycling . Statistics from different geographical regions and times are not comparable. Even basic definitions such as recycling rate and paper consumption are not uniform. There is a pressing need to develop a uniform system of terms and definitions. Abstract: A global, comprehensive review of terms and definitions related to paper recycling was conducted in this article. Terms and definitions related to paper recycling have varied in the course of time. Different terms and different definitions for the same thing are being used in different geographical regions and by different organizations. Definitions are different based on varying conceptions of waste paper as a raw material . Definitions of how to make various calculations related to paper recycling activity are inconsistent. Even such fundamental basic definitions like how to calculate recycling rate and paper consumption are not uniform. It could be concluded that there is no uniform system of terms and definitions related to paper recycling and the implications of this deficiency are profound. For example, it is difficult to reliably compare with each other statistics from different times and from different geographical regions. It is not possible to measure if targets for recycling activities are met if the terms describing the targets are not uniformly defined. In cases of reporting data for recycling targets, the lack of uniform terminology can, for example, impede the necessary transparency between different stakeholders and may allow for deception. The authors conclude there is a pressing need to develop a uniform system of terms and definition for terms related to paper recycling .